Efficacy and safety of 177Lu-DOTATATE targeted therapy in advanced/metastatic pulmonary neuroendocrine tumors: A systematic review and meta-analysis - Ma, Jiao; Hu, Xin; Li, Lanying; Rao, Zijuan; Zhang, Chunyin (Frontiers in Oncology, 2022)
Objective: To perform a meta-analysis of the efficacy and safety about 177Lu-DOTATATE therapy for advanced/metastatic pNETs based on the current clinical evidence. Methods: This systematic review follows the PRISMA guideline. Search PubMed, Medline, EMBASE and CNKI, VIP, Wanfang databases, from establishment to June 2022, on the study of 177Lu-DOTATATE for advanced /metastatic pNETs, the primary endpoint was to evaluate the treatment effect through DRRs and DCRs . Secondary endpoint included assessment of OS, PFS, and treatment-related adverse events across all studies. Two researchers conducted literature screening, data extraction and quality evaluation according to the inclusion and exclusion criterias. Meta-analysis was performed using stata16.0 software, and the datas were merged and displayed using forest graphs. Results: A total of 5 studies, 174 patients，on 177Lu-DOTATATE for advanced /metastatic pNETs were included. The pools of DRRs and DCRs were 24% (95% CI: 15% to 32%) and 77% (95% CI: 62% to 92%), respectively. The pool of OS was 48.78 months (95% CI: 41-56.57 months) and the pool of PFS was 21.59 months (95% CI: 17.65-25.53 months). In all studies, the most common side effect of treatment was hematological toxicity. In 174 patients, hematological toxicity of grade III accounted for 4.0% (7/174), and only 4.0% (7/174) and 1.0% (2/174) of patients had mild nephrotoxicity and hepatotoxicity. Gastrointestinal adverse reactions in 3% (6/174), nausea in 2% (3/174), superior vena cava occlusion in 0.5% (1/174). Conclusion: 177Lu-DOTATATE is effective and safe for advanced /metastatic pNETs, which can delay the progression of the disease,may improve patients' survival, and has low treatment-related toxicity and high safety. However, its efficacy and safety need to be further evaluated in high-quality, multicenter randomized controlled trials in the future.